The Effects Of Brand Image In Purchasing Of Online Marketing Among University Students - Ahamat, Amiruddin; Shahkat Ali, Muhamad Sham; Zahari, Nor Akmal Nabihah (Inderscience Enterprises Ltd., 2018)
The brand image can give a huge impact to the marketer and the consumer as the buyer of the product. The brand image factor can also motivate consumer in their purchasing decision because the brand image may reflect the product itself. The purpose of this paper is to elaborate the relation between the awareness of a brand and the intention of buying a brand. There were several brand image factors highlighted in this research which is pricing, advertisement, brand name and quality of the product. A quantitative method was used through an online questionnaire in order to prove the factors that can affect the brand image in online marketing among university students. Based on the results, several factors were identified as the contributing effect on a brand image which is the price of a product, advertisement of product and the quality of a product.